Social role effects on gender stereotyping in Germany and Japan. Issue 1 (22nd January 2014) - Steinmetz, Janina; Bosak, Janine; Sczesny, Sabine; Eagly, Alice H.
<x xml:space="preserve">Abstract</x> Social role theory postulates that gender stereotypes are restrained for men and women observed in the same social role. Cultural differences in the valuation of communal attributes might moderate this effect. To examine this possibility, 288 participants (144 German, 144 Japanese) estimated the communal and agentic attributes of an average man or woman described in a male‐dominated role, a female‐dominated role, or without role information. We hypothesized and found that in Germany and Japan, participants perceived men as more agentic than women without role information and as similarly agentic in the same role. However, for communion, German and Japanese participants reacted differently. German participants perceived women as more communal than men without role information and in male‐dominated roles and perceived men as more communal than women in female‐dominated roles. Japanese participants perceived all targets as similarly communal, regardless of role or gender, suggesting that communion is generally expected in Japan.